Poetry of Pavel Oláh - Oláh, Pavel (Romano džaniben, 2020)
Three poems by an author writing in Romani, Czech, and Polish. Within the issue, they also serve as an example of the south-central dialect of Romani, which is the subject of a text in the reviewed section.